IMPROVING THE ELEVENTH GRADE STUDENTS’ WRITING ABILITY THROUGH PROBLEM BASED LEARNING AT SMKN 1 PENUKAL - Candra Dewi Cahyaningrum; Masagus Firdaus; Mulyadi (Universitas PGRI Palembang, 2024)
The purpose of this study was to improve the writing abilities of eleventh grade students at SMKN 1 Penukal by using Problem-Based Learning in the academic year 2023–2024. 34 students participated in the study, which used a Collaborative Classroom Action Research (CAR) design. The writer and the English instructor worked together as partners on the project. The research employed the Kemmis and McTaggart paradigm, which included three cycles of three meetings each for the purposes of planning, acting, observing, and reflecting. Tests and observation were used in the gathering of data. The findings demonstrated that students' writing skills had improved; their mean scores increased from 63.82 in the first research to 89.71 in the third cycle, above the Minimum Mastery Criterion (KKM) of 75. The English teacher's affirmative reaction demonstrated the effectiveness of the activity that was put into place. Finally, it can be said that problem-based learning improved the writing skills of students.